THE EFFECTS OF PROBLEM-BASED LEARNING ON BIOLOGY LEARNING ACHIEVEMENT: A RANDOMIZED CONTROLLED TRIAL - Saleh, Andi Rahmat; Syamsiah, Syamsiah; Pabisa, Vesly Hardianti (Universitas Tanjungpura, 2023)
Problem Based Learning is one of the options of the instructional one that can be implemented in the K13 Curriculum (Kurikulum 2013) or the Independent Curriculum (Kurikulum Merdeka). This study aims to determine the effect of the Problem Based Learning on the learning outcomes of Class X students in biology subject. The type of research was a quantitative study with a posttest only control group design. The research population was all students of three classes X IPA at SMA Negeri 7 Sa'dan Toraja Utara in the odd semester of the 2022/2023 academic year. Through the random sampling technique, two classes were obtained that would serve as control and experimental classes, namely class X IPA 2 and X IPA 1 with a total of 54 students. Data collection was carried out through a learning achievement test instrument in the form of multiple choice of 30 numbers. The learning outcomes data were then analyzed descriptively and inferentially. The results showed that the average learning outcomes for the experimental class were in the average category while the control class was in the poor category. T test was used to confirm the hypothesis. The result shows the sig. (2 tailed) of 0.009 which means less than 0.05. Based on the results it can be concluded that Problem Based Learning is able to have a positive influence on the learning outcomes of class X students in biology subject.